The Effect of Locus of Internal Control on The Ability to Maintain a MicroBusiness in The Pandemic Time Covid-19: Pengaruh Locus of Internal Control terhadap Kemampuan Mempertahankan Bisnis Wirausaha Mikro di Masa Pandemi Covid-19 - Muharika Dewi; Riri Putri Dika; Vivi Puspita Sari (International Journal of Management and Business (IJMB), 2020)
Maintaining business in times of multidimensional crisis due to the COVID 19 pandemic is something that is difficult for micro-entrepreneurs to do. The character of entrepreneurs affects every decision that must be made in a situation full of uncertainty. This paper reveals the relationship between locus if internal control (LoC) characteristics and the ability to sustain micro-entrepreneurial ventures. Research with a quantitative approach, the data were analyzed descriptively and associatively using the Pearson correlation formula, and contribution analysis. The instrument uses a questionnaire, the sample is entrepreneurs with the strength of micro-scale capital taken by random sampling using incidental sampling techniques through google form data collection. The analysis shows that the micro-entrepreneurial business conditions at a score of 63.8% are categorized as bad, while LoC has a score of 58.4% in the bad category, the correlation results have a positive direction of 0.726, the value of X's contribution to Y is 52.6%.